Effects of nutrition on production and reproduction of dairy cows in Bangladesh (Bangladesh Veterinarian, 2010)
Sixty-eight cows in group A were fed 63.9 megajoules (MJ)/day, 66 in B were fed52.9, and 66 in C were fed 51.1 MJ/day. The mean (± SD) services per pregnancy of cowsin groups A, B and C were 1.7 ± 0.7, 1.9 ± 0.6 and 2.5 ± 0.9, respectively. The mean calvingto 1stfirst service intervals were 158.1 ± 51.5, 171.0 ± 59.0 and 200.0 ± 50.3 days,respectively. The mean milk yields were 5.8 ± 2.6, 4.5 ± 1.9 and 4.3 ± 1.9 litres/ day,respectively. Pregnancy rate was significantly (P